Cover Image, Volume 122, Number 12, December 2021. Issue 12 (10th December 2021) - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp
Abstract : Front Cover : The cover image is based on the Research Article Computational decomposition reveals reshaping of the SARS‐CoV‐2–ACE2 interface among viral variants expressing the N501Y mutation by Eileen Socher et al., https://doi.org/10.1002/jcb.30142 .